The Analysis of Conflict of the Main Character in the Movie “I am Sam” - Nudhi Angga Bramaditha, Ketut; Qomariana, Yana (Udayana Journal of Social Sciences and Humanities; Vol 4 No 2 (2020): UJoSSH, September 2020DO - 10.24843/UJoSSH.2020.v04.i02.p06, 2020)
The title of this paper is The Analysis of Conflict of the Main Character in the Movie “I am Sam” . This study focuses on describing the category and function of the main character and the external conflicts of the main character. The movie I am Sam was analyzed by categorizing the main character. The data of this study were taken from a movie entitled I Am Sam . The data were collected through documentary method, by watching the movie and were then by marking and taking notes of parts of the movie which are related to the study. The data then were categorized based on the theories. The American drama film I am Sam which is the compelling story of Sam, a mentally-challenged father raising his daughter Lucy with the help of a unique group of friends. The category and function were analyzed based on the theory proposed by Wellek and Warren (1995: 227) who divide character into two types, static and dynamic characters; the analysis also included Protagonist and Antagonist characters. The conflict was analyzed based on the theory of literature proposed by Kenney (1996) who divides conflicts into two types, external and internal conflicts. But in the movie, the only external conflict occurs. The analysis brought some conclusions. Sam, as the main character, has a mental disorder, described as a really kind-hearted person. He also had a big willing, even so many challenges he should pass to live with his daughter, he still tried so hard to do it. After so many people hurt his feeling, he was still kind and did not do bad things to them. The conflicts all passed with him being a kind and honest person.